If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7y-3=2y-3
We move all terms to the left:
7y-3-(2y-3)=0
We get rid of parentheses
7y-2y+3-3=0
We add all the numbers together, and all the variables
5y=0
y=0/5
y=0
| (3x+16)+(2x+8)+(8x-18)=180 | | -6r+15–5+4r=6 | | 1x-11=1 | | 4/x+1=−3/x+2 | | 45+7x=4x45+7x=4x | | 1/3x+3=-2= | | 3(n+5)−10=−13 | | 65x-12=43 | | 2c+1=6c | | 10z+13.27=73.27 | | 5x-4+3x+5=x-2+3x+7 | | 8+4c=-4c | | 12x72= | | 3y+2-6y=8+3(y+2) | | x²+13=38 | | n(-8)=5(n-9) | | 5(-8-2x)=-21 | | 7x+1=5+2x | | 7m-3=11m+2 | | 10−4h=6h | | 55y=6(9y-7)= | | b3+ 8=12 | | x28=17 | | 132=(12y+4)+(9y+2) | | x+7.9=5.4 | | 0=2n^2+3n-1890 | | X+5+3x-7=18 | | (3+x)=5 | | 1/4(5x+16/3)-2/3(4/4+1/2=-5 | | 4-7n+7=-10 | | x+2=17−4x | | 124-n=113n= |